Hippocampal sparing radiotherapy for glioblastoma patients: a planning study using volumetric modulated arc therapy. Issue 1 (December 2016) - Hofmaier, Jan; Kantz, Steffi; Söhn, Matthias; Dohm, Oliver; Bächle, Stefan; Alber, Markus; Parodi, Katia; Belka, Claus; Niyazi, Maximilian
Abstract Background The purpose of this study is to investigate the potential to reduce exposure of the contralateral hippocampus in radiotherapy for glioblastoma using volumetric modulated arc therapy (VMAT). Methods Datasets of 27 patients who had received 3D conformal radiotherapy (3D-CRT) for glioblastoma with a prescribed dose of 60Gy in fractions of 2Gy were included in this planning study. VMAT plans were optimized with the aim to reduce the dose to the contralateral hippocampus as much as possible without compromising other parameters. Hippocampal dose and treatment parameters were compared to the 3D-CRT plans using the Wilcoxon signed-rank test. The influence of tumour location and PTV size on the hippocampal dose was investigated with the Mann–Whitney-U -test and Spearman's rank correlation coefficient. Results The median reduction of the contralateral hippocampus generalized equivalent uniform dose (gEUD) with VMAT was 36 % compared to the original 3D-CRT plans (p < 0.05). Other dose parameters were maintained or improved. The median V30Gy brain could be reduced by 17.9 % (p < 0.05). For VMAT, a parietal and a non-temporal tumour localisation as well as a larger PTV size were predictors for a higher hippocampal dose (p < 0.05). Conclusions Using VMAT, a substantial reduction of the radiotherapy dose to the contralateral hippocampus for patients with glioblastoma is feasible without compromising other treatment parameters. For larger PTV sizes, less sparing can be achieved. Whether this approach is able to preserve the neurocognitive status without compromising the oncological outcome needs to be investigated in the setting of prospective clinical trials.